Synthesis and photophysics behaviour in AOT/cyclohexane w/o microemulsions of a new benzo[a]phenoxazinium chloride with 3-((3-chloropropyl)disulfanyl)propyl)amino group - Raju, B. Rama (2012)
Fluorescent probes for labelling of biomolecules are widely used for various purposes. In this context we have efficiently synthesised a new benzo[a]phenoxazinium chloride possessing the 3-((3-chloropropyl)disulfanyl)propyl)amino group at position 5. The disulfide bond can be cleaved under mild basic conditions to afford the free thiol group, and consequently this heterocycle could act as a capping layer for the passivation of semiconductor QDs. The location of the new benzo[a]phenoxazinium chloride in AOT/cyclohexane was studied by fluorescence spectroscopy, since this microheterogeneous structures are frequently used for nanoparticle synthesis.